Parity and Metabolic Syndrome Risk: A Systematic Review and Meta-Analysis of 15 Observational Studies With 62,095 Women - Sun, Ming-Hui; Wen, Zhao-Yan; Wang, Ran; Gao, Chang; Yin, Jia-Li; Chang, Yu-Jiao; Wu, Qi-Jun; Zhao, Yu-Hong (Frontiers in Medicine, 2022)
Background: Epidemiological studies have provided inconsistent evidence of the association between parity and metabolic syndrome (MetS) risk. We conducted this first systematic review and meta-analysis to comprehensively and precisely quantify this topic. Methods: Comprehensive searches of PubMed, EMBASE, and Web of Science databases were conducted to identify observational studies of the association between parity and MetS risk up to January 30, 2022. Study inclusion, data extraction, and quality assessment were checked and reviewed by two authors independently. Random-effects models were used to estimate pooled odds ratios (ORs) and 95% confidence intervals (CIs). We also conducted publication bias, subgroup, sensitivity and meta-regression analyses. This study has been registered with PROSPERO (CRD42022307703). Results: Two high-quality cohort and thirteen medium-quality cross-sectional studies involving 62,095 women were finally included. For the ever parity versus nulliparous, the pooled OR was 1.31 (95%CI=0.91-1.88, I2=72.6%, n=3). For the highest versus lowest parity number, the pooled OR was 1.38 (95%CI=1.22-1.57, I2=60.7%, n=12). For the dose-response analysis, the pooled OR of MetS for each increment of one live birth was 1.12 (95%CI=1.05-1.19, I2=78.6%, n=6). These findings were robust across subgroup and sensitivity analyses. No evidence of heterogeneity between subgroups was indicated by meta-regression analyses. Conclusion: The findings suggested that parity was associated with an increased risk of MetS. Further large prospective cohort studies are needed to verify our finding.